Aluminum influence on in vitro germination of isolated embryos of two Vochysiaceae Al-accumulating species - Nogueira, Matheus Armelin [UNESP]; Gavassi, Marina Alves [UNESP]; Cardoso, Jean Carlos; Habermann, Gustavo [UNESP] (Springer Nature, 2024)
Qualea grandiflora and Vochysia tucanorum (Vochysiaceae) are aluminum-accumulating woody species from the Cerrado vegetation in South America and retain aluminum (Al) in their seeds. Studies suggest Al dependency for these species, but no physiological role has been ascribed to Al in their seeds. Based on a previous study that showed ethylene (Et) improves the germination of intact seeds of V. tucanorum, we inoculated their isolated embryos in a culture medium with increasing Al concentrations and under Et influence (seeds were pretreated with Ethrel®, an Et-releasing compound) to see how Et effects and Al interact during germination. Despite showing more than 8,000 (Q. grandiflora) and 32,000 (V. tucanorum) mg Al kg−1 seed, both species, but mainly V. tucanorum embryos, germinated better in an Al-enriched medium. Ethylene induced germination of V. tucanorum embryos when Al was absent in the medium, indicating an effect of Et on the germination of isolated embryos of this species. Embryos of Q. grandiflora germinated independently of Al in the medium and Et did not influence their germination. Both species seemed to transfer the Al from seeds to their seedlings, highlighting the importance of Al during seed germination of these Al-accumulating species.
Keywords: Al3+; Brazilian savanna; Culture medium; Ethylene; Rescued embryo